Investigating the Role of TGF-β Signaling Pathways in Human Corneal Endothelial Cell Primary Culture - Inès Aouimeur; Tomy Sagnial; Louise Coulomb; Corantin Maurin; Justin Thomas; Pierre Forestier; Sandrine Ninotta; Chantal Perrache; Fabien Forest; Philippe Gain; Gilles Thuret; Zhiguo He (Cells, 2023)
Corneal endothelial diseases are the leading cause of corneal transplantation. The global shortage of donor corneas has resulted in the investigation of alternative methods, such as cell therapy and tissue-engineered endothelial keratoplasty (TEEK), using primary cultures of human corneal endothelial cells (hCECs). The main challenge is optimizing the hCEC culture process to increase the endothelial cell density (ECD) and overall yield while preventing endothelial–mesenchymal transition (EndMT). Fetal bovine serum (FBS) is necessary for hCEC expansion but contains TGF-βs, which have been shown to be detrimental to hCECs. Therefore, we investigated various TGF-β signaling pathways using inhibitors to improve hCEC culture. Initially, we confirmed that TGF-β1, 2, and 3 induced EndMT on confluent hCECs without FBS. Using this TGF-β-induced EndMT model, we validated NCAM as a reliable biomarker to assess EndMT. We then demonstrated that, in a culture medium containing 8% FBS for hCEC expansion, TGF-β1 and 3, but not 2, significantly reduced the ECD and caused EndMT. TGF-β receptor inhibition had an anti-EndMT effect. Inhibition of the ROCK pathway, notably that of the P38 MAPK pathway, increased the ECD, while inhibition of the ERK pathway decreased the ECD. In conclusion, the presence of TGF-β1 and 3 in 8% FBS leads to a reduction in ECD and induces EndMT. The use of SB431542 or LY2109761 may prevent EndMT, while Y27632 or Ripasudil, and SB203580 or SB202190, can increase the ECD.